Entrepreneurial Knowledge, Self-Efficacy, and The Impact of The Environment on The Entrepreneurial Interests in Electronic Engineering Department Students - Elsa Sabrina; Ganefri; Asmar Yulastri; Ambiyar (The Indonesian Journal of Computer Science, 2023)
The purpose of this study was to demonstrate the potential impact of entrepreneurial knowledge, self-efficacy, and environmental factors on entrepreneurial interest. This study uses an explanatory research approach. The population is students of Universitas Negeri Padang, Department of Electronics Engineering, using a purposive sampling technique. A sample of 80 respondents was determined using accidental sampling technique. Data was collected using questionnaires and tests. Then the method used is purposive sampling and data collection using accidental sampling. The analytical tool used is multiple linear regression analysis. The results of the study show that entrepreneurship education, entrepreneurial self-efficacy and environmental factors influence interest in entrepreneurship